Penerapan Blended Learning Berbasis Kelompok terhadap Keterampilan Menyimak - Wahyudin; Fadhilah Zamzam; Grace Novenasari Manurung (Jurnal Kreatif Online, 2021)
This study aims to find out the influence of group-based blended learning towards the listening skill. The research design used was experimental one group pre- and post-tests. The study sample consisted of 22 students of class X SMA An Nur Buuts Palu which was drawn purposively. Learners were given pretest and then treatment both face-to-face teaching mode and virtually and posttest after the treatment conducted. The data were analyzed using Descriptive Statistics Analysis through SPSS for windows version 22. The results of the data analysis show that the mean of the pretest (N = 23) is 34.96 and the standard deviation is 3,391, the mean of the posttest (N = 23) is 42.09 and the standard deviation is 4,368. The results of pretest and posttest are normally distributed based on the results of the Shapiro-Wilk analysis (N < 50) sig. 0.070 > 0.05 for pretest and 0.064 > 0.05 for posttest. From the results of the Paired Samples T-Test test, it is found that the mean of the pretest (34.96) is lower than the mean of the posttest (42.09), the correlation coefficient is sig. 0.059 > 0.05 with a significance level of sig. 0.791 > 0.05, and the Paired Samples T-Test results show a significance value of sig. (2-tailed) 0.000 < 0.05. This data shows that there is a significant difference between the results of the pretest and the posttest. It implies that the application of group-based blended learning significantly influences the listening skills of the students.